احلب ة السوداء يف ضوء السنةّالنبويةّوعلمّالطبّ - Mesbahul Hoque; Abdoul Karim Toure; Zulhilmi Mohamed Nor; Shumsudin Yabi (UNIVERSITI SAINS ISLAM MALAYSIA, 2024)
Journal of Islamic Social Sciences and Humanities. Volume 30 Issue 1 Page (25–38)